The Development of Residential and Commercial Real Estate, and Economic Development in Polish Voivodships - Jacek Łaszek; Robert Leszczyński; Krzysztof Olszewski (Barometr Regionalny)
The article presents the development of residential and commercial real estate in Poland and its 16 voivodships. This is closely linked to the economic development of the regions. The first part shows how the stock of this real estate grew on a national scale and how their values changed. The second part analyzes the change in the stock of residential and commercial real estate (office and commercial property) in particular voivodships. Dependencies are noted. The residential areas developed in a similar manner in different voivodships, with supply increasing with a delay of about two years after economic growth. This can be explained by the fact that when the economic situation of households improves, they want to improve their housing situation. On the other hand, the development of commercial space is accompanied by economic development with a one-year delay. Taking into account that the process of physical construction takes about 2 years, this implies the existence of a strong endogeneity between employment in the service or retail sectors and income growth. This endogeneity acts as feedback (revenue growth is an increase in surface area, which in turn generates income), so the cause and effect have slight time delays. The development of commercial real estate in individual voivodships intensified in different periods. This is probably connected with the inflow of foreign capital, which first came to Warsaw and the Warsaw agglomeration, then to large centers (Trójmiasto, Poznań) and only with some delay to other voivodships.